17‐4: Effective Architectural Lighting with Freeform Optics. Issue 1 (May 2016) - Zhu, Ruidong; Hong, Qi; Zhang, Hongxia; Wu, Shin‐Tson
Abstract : We designed freeform reflectors for architectural lighting applications. Compared with conventional luminaries, these freeform luminaries can effectively distribute light fluxes over target surfaces, and generate appropriate illumination patterns for comfortable environments.